Magnetophoretic manipulation in microsystem using carbonyl iron-polydimethylsiloxane microstructures - Faivre, Magalie (AIP Publishing LLC, 2014)
This paper reports the use of a recent composite material, noted hereafter i-PDMS, made of carbonyl iron microparticles mixed in a PolyDiMethylSiloxane (PDMS) matrix, for magnetophoretic functions such as capture and separation of magnetic species. We demonstrated that this composite which combine the advantages of both components, can locally generate high gradients of magnetic field when placed between two permanent magnets. After evaluating the magnetic susceptibility of the material as a function of the doping ratio, we investigated the molding resolution offered by i-PDMS to obtain microstructures of various sizes and shapes. Then, we implemented 500 μm i-PDMS microstructures in a microfluidic channel and studied the influence of flow rate on the deviation and trapping of superparamagnetic beads flowing at the neighborhood of the composite material. We characterized the attraction of the magnetic composite by measuring the distance from the i-PDMS microstructure, at which the beads are either deviated or captured. Finally, we demonstrated the interest of i-PDMS to perform magnetophoretic functions in microsystems for biological applications by performing capture of magnetically labeled cells.